Pogledi na metaforo - Čeh Steger, Jožica (Jezik in slovstvo, 2005)
The article describes various views on metaphor, as discussed by the substitutional, comparative, interactional and cognitive theory of metaphor. The author points out that the cognitive theory instigated many radical changes in the traditional understanding of metaphor, although some aspects of the cognitive approach can be found much earlier, especially in the interactional theory of metaphor. The cognitive theory cannot make a final rejection of the traditional understanding of metaphor, since as a theory of conceptual metaphor it does not have the answers to many questions concerning linguistic metaphor and its role in various text types.
Keywords: literarna teorija; literarne študije; literary theory; metafora; metaforika; metaphor